2022
DOI: 10.1002/cphc.202100910
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Layer Deposited Ti2O3 Thin Films

Abstract: Ti 2 O 3 thin films have been prepared through atomic layer deposition and subjected to electrical resistivity measurements as a function of temperature. The as-prepared films were stable for up to three weeks. In Ti 2 O 3 thin films, the insulator-metal transition is observed at ~80 K, with nearly 3-4 orders of magnitude change in resistivity. The anomalous increase in electrical resistivity in the films is in accordance with the twoband model. However, the energy interval between the bands depending on the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…They exhibit MITs as well as semiconductor-metal transitions. The electrical conductivity of Ti 2 O 3 increases from ~10 3 to ~10 4 S/m as it transitions from the insulator phase to metallic phase at ~450 K. However, unlike VO 2 , it does not undergo crystal structure transformation [99,100]. TiO 2 undergoes metal-insulator transition caused by reduction under high-temperature and low oxygen partial pressure.…”
Section: Titanium Oxidementioning
confidence: 99%
See 1 more Smart Citation
“…They exhibit MITs as well as semiconductor-metal transitions. The electrical conductivity of Ti 2 O 3 increases from ~10 3 to ~10 4 S/m as it transitions from the insulator phase to metallic phase at ~450 K. However, unlike VO 2 , it does not undergo crystal structure transformation [99,100]. TiO 2 undergoes metal-insulator transition caused by reduction under high-temperature and low oxygen partial pressure.…”
Section: Titanium Oxidementioning
confidence: 99%
“…Some first-principles calculations exploring these transitions were investigated to help guide the growth and development of the series [103]. In these calculations, it was found that the monoclinic angle of β-Ti 3 O 5 was 91.1 VO2, it does not undergo crystal structure transformation [99,100]. TiO2 undergoes metalinsulator transition caused by reduction under high-temperature and low oxygen partial pressure.…”
Section: Titanium Oxidementioning
confidence: 99%